Short-course systemic corticosteroids in asthma: striking the balance between efficacy and safety. (3rd April 2020) - Price, David; Castro, Mario; Bourdin, Arnaud; Fucile, Sebastian; Altman, Pablo
Short courses of systemic corticosteroids (SCS), both oral and injectable, are very effective for the resolution of acute asthma symptoms, including exacerbations. However, the benefits of SCS, even short courses, must be balanced against the impact of their side-effects. While the adverse consequences of long-term use are widely recognised, there appears to be a perception in the medical community that short courses of SCS are safe. Limited but growing evidence in the literature suggests that even very brief dosing periods (3–7 days) of SCS are enough to cause significantly negative outcomes for patients. Short courses of SCS are associated with increased risk of adverse events including loss of bone density, hypertension and gastrointestinal ulcers/bleeds, in addition to serious impacts on mental health. Strategies to improve asthma control are recommended, including: 1) as-needed combination therapies in mild asthma; 2) risk factor reduction; 3) improving adherence/inhaler technique; 4) earlier initiation of add-on therapies; 5) use of biologics in appropriate patients; 6) development of new therapies to better control the disease; and 7) widespread education of the medical community. We propose that patients and primary care physicians should consider a cumulative SCS dose of 1 g per year as a highly relevant and easy-to-recall threshold. Inappropriate use of systemic corticosteroids in asthma may add to disease burden. Even short-term, intermittent use is associated with health risks. Strategies to improve asthma control and reduce inappropriate use of systemic corticosteroids are needed. https://bit.ly/3bdieam